Using copper-coated round rod electrodes at various depths in freshwater marshes - Putra, Dian Eka; Nawawi, Zainuddin; Jambak, M. Irfan (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: High-voltage electrical equipment requires grounding installation to protect lives in freshwater swamps with a hydrogen potential of 6.75. To build a grounding structure, it is necessary to know the resistance value and grounding materials, namely, copper-coated rod electrodes at different depths. Research methodology: The research was conducted in a freshwater swamp close to the shampooing substation using field observations and direct measurements of soil resistance values, followed by a literature review and comparisons using COMSOL simulation and FEM Analysis. Results: The results of direct research and simulations indicate that to accomplish a grounding resistance value < 5 ? according to the PUIL 2011 standard for a single-rod system made of copper, it is necessary to optimize the depth of the grounding electrode within a range of 10 m, which differs from the simulation results of ground resistance measurement and the Comsol application. The percentage error was 1.05%. Conclusion: The findings demonstrate that increasing electrode depth effectively reduces grounding resistance in freshwater swamp environments, though variations exist between field and simulated data. Limitations: This study analyzed the results of measurements and grounding analysis using COMSOL Multiphysics at a depth of 1 m for a particular type of copper-coated round rod electrode at depths of 1, 1.5, and 2 m. Contributions: The results of this study offer information on the usefulness of grounding resistance in freshwater wetlands with a pH greater than 6, where several rod electrode types can be utilized for comparison in future research.